(untitled) (Research, Society and Development, 2021)
Cervical cancer is the fourth most frequent type of cancer affecting women worldwide and the third most common cancer affecting women in Brazil. This neoplasm is caused by human papillomavirus (HPV) infection and its prevention is reached through HPV vaccination and screening tests. However, in 2020, due to COVID-19 pandemic, the screening of this cancer was affected by restrictions in health services. This article aims to demonstrate the impact of the pandemic on cervical cancer screening in Teresina - PI, through a comparative analysis of data of the number of oncotic cytologies performed between March 2019 and February 2021 and the number of COVID-19 cases registered between March 2020 and February 2021. It was observed a reduction in screening for the mentioned cancer coinciding with the period of restriction in health services. Therefore, it is possible to state that the pandemic had a great impact on cervical cancer screening, making it important to actively search for patients who had lesions that needed follow-up before the pandemic and for women who did not seek health care in 2020. Moreover, it is important to take into account to change the test currently used for cervical cancer screening in Brazil in order to allow for a longer follow-up interval.